Improving Environmental Literacy and Waste Management Skills among ‘Aisyiyah Orphanage through Recycled Plastic Bottle Utilization - Kemala Sari, Meidita; Siregar, Sri Hilma; Irma, Wirdati; Nasution, Hasmalina; Isnaniar, Isnaniar; Amini, Rahmi; Gasril, Pratiwi; Gesriantuti, Novia; Norlita, Wiwik; Herlinda, Susi (LPPM UMRI, 2026)
This community service program aimed to improve environmental literacy and waste management skills among children at ‘Aisyiyah Orphanage. The program involved 45 participants from elementary, junior high, and senior high school levels. The activity was conducted in response to the low level of awareness regarding proper waste management and the negative impacts of waste on environmental quality and public health. The implementation methods included educational counseling on environmental issues and waste management, interactive discussions, and hands-on training in transforming used plastic bottles into flower pots. Evaluation was carried out through participant observation and assessments of knowledge before and after the activity. The results demonstrated a significant improvement in participants’ understanding of waste classification, the environmental and health impacts of waste, and the importance of the Reduce, Reuse, and Recycle (3R) principles. Furthermore, participants successfully converted used plastic bottles into functional flower pots, demonstrating enhanced practical waste management skills. The program offered an engaging learning experience that fostered environmentally responsible attitudes and behaviors among the children at the orphanage. Similar initiatives should be implemented continuously to strengthen sustainable waste management practices and promote environmental stewardship among young generations